Procedures for the generation of potato tuber families from true seed - Mihovilovich, E.; Amoros, W.; Bonierbale, Merideth W. (International Potato Center, 2017)
This protocol attempts to provide a detailed description of the procedures to produce tuber families in order to orient and facilitate potato research toward more efficient breeding product achievements.